Why no board-level employee representation in Italy? Actor preferences and political ideologies. (September 2019) - Leonardi, Salvo; Gottardi, Donata
Unlike most continental EU countries, Italy lacks any system of board-level employee representation, despite a specific article in the 1948 Constitution. Hence, involvement and participation remain limited to the sphere of contractually established information and consultation rights, primarily because of the reluctance of the social partners to establish reciprocal responsibilities by law. Employers feared that this would limit their property rights and prerogatives, unions that it would restrict their own autonomy. After a long history of confrontational industrial relations, there has been a shift towards participatory approaches, but in a distinctive way. We present an overview of the historical background and the cultures and practices of the main actors, the Italian approach to industrial democracy, the influence of other national models and the current debates and legislative proposals. We conclude by assessing the opportunities for and obstacles to real change in the future.